Comparison of Penta Real estate´s commercial projects´ achievability between Prague and Bratislava - Faltus, Jakub; Černá, Iveta, 1979-; Křenková, Eva; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis aims to asses the business climate surrounding the real estate development markets in Prague and Bratislava based on projects by Penta Real Estate. The thesis will answer questions such as: Which real estate development markets in Prague or Bratislava is more convenient for real estate developers? Which of the markets is more open for new construction? What are the significant factors influencing the approval and construction of a project? These research questions are answered by analyzing the economic, legal, and political backgrounds of two Penta Real Estate projects. All influences affecting the projects are summarized in the term: project achievability. The assessment will be done via an analysis of the Macroclimate and Microclimate surrounding the projects and the use of 3 "indicators." The indicators are split into Project Bureaucracy, Project Timeline, and Project Financial Expense. They will provide a base for an evaluation system with which an assumption will be made whether the real estate market in Prague or Bratislava offers a more suitable business environment at this time.
Vedoucí práce: Iveta Černá
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses